A New Integration Approach to support the Development of Build-time Micro Frontend Architecture Applications - Moraes, Fernando Rodrigues de; Affonso, Frank José (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2024)
The Micro Frontend Architecture (MFA) is an innovative, scalable, and flexible architectural model supporting frontend software development. Despite the advantages of this architectural model, technologies that depend on packaging applications in compile time benefit from MFA using a build-time approach by splitting Micro Frontend Applications (MFApps) in packages, which makes this application incapable of performing a runtime interpretation of other MFApps. This paper introduces a new integration approach to support the development of build-time MFApps to overcome limitations related to the coupling of these applications. The proposed approach employs the concept of remote component rendering and the Backend for Frontend pattern to solve continuous delivery issues, provide runtime integration, and help teams scale their development process of MFApps. As a result, we observed that our integration approach enables the developers to work with MFA in a build-time approach as a runtime integration of MFApps.